Urban bikeway design guide (Island Press/Center for Resource Economics, 2014)
The NACTO Urban Bikeway Design Guide, Second Edition, is based on the experience of the best cycling cities in the world. Completely re-designed with an accessible, four-color layout, this second edition continues to build upon the fast-changing state of the practice at the local level. The designs in this book were developed by cities for cities, since unique urban streets require innovative solutions. To create the Guide, the authors conducted an extensive worldwide literature search from design guidelines and real-life experience. They worked closely with a panel of urban bikeway planning professionals from NACTO member cities and from numerous other cities worldwide, as well as traffic engineers, planners, and academics with deep experience in urban bikeway applications. The Guide offers substantive guidance for cities seeking to improve bicycle transportation in places where competing demands for the use of the right-of-way present unique challenges. First and foremost, the NACTO Urban Bikeway Design Guide, Second Edition will help practitioners make good decisions about urban bikeway design. The treatments outlined in this updated Guide are based on real-life experience in the world's most bicycle friendly cities and have been selected because of their utility in helping cities meet their goals related to bicycle transportation. Praised by Former Transportation Secretary Ray LaHood as an "extraordinary piece of work," the Guide is an indispensable tool every planner must have for their daily transportation design work.